Elevated Microsatellite Alterations at Selected Tetranucleotide Repeats (EMAST) and Microsatellite Instability in Patients with Colorectal Cancer and Its Clinical Features - Lee, H.S.; Park, K.U.; Kim, D.-W.; lhn, M.H.; Kim, W.H.; Seo, A.N.; Chang, H.E.; Nam, S.K.; Lee, S.Y.; Oh, H.-K.; Kang, S.-B. (Current Molecular Medicine, 2016)
Purpose: Recently, a different type of microsatellite instability (MSI) instability designated ‘elevated microsatellite alterations at selected tetranucleotide repeats’ (EMAST) has been reported in several neoplasms, but its clinical implications remain unclear. We aimed to determine the relationships among EMAST, MSI and clinicopathologic characteristics, including oncologic outcomes, in colorectal cancer (CRC). Materials and Methods: We evaluated 100 sporadic CRC cases subjected to surgery using five markers (MYCL1, D9S242, D20S85, D8S321, and D20S82) for EMAST and the Bethesda panel for MSI status. Immunohistochemical detection of hMSH3, c-erbB2, EGFR and thymidylate synthase was performed. Clinical characteristics and prognostic relevance were assessed. Results: We identified 22 EMAST-positive tumors (22.0%) and 32 MSI-high (MSI-H) tumors (32.0%). EMAST was more frequent in colon cancer than rectal cancer (p=0.033), and associated with MSI-H phenotype (p<0.001), low expression of hMSH3 (p=0.004), and overexpression of thymidylate synthase (p=0.006). Among the 38 MSI-L tumors, only one (4.5%) showed EMAST. Long-term oncologic results in terms of overall and disease-free survival were similar between EMAST and non-EMAST tumors. Conclusion: EMAST is more closely related to MSI-H than MSI-L or MSS status. The clinical and molecular characteristics of EMAST were distinct in terms of tumor location, thymidylate synthase expression, MSI status and hMSH3 expression. Our preliminary findings support the utility of EMAST as a new potential classifier in CRC.
Keywords: Colorectal cancer